La FIJL dans la lutte antifranquiste (1960-1974) - Antoni Rossi Trafach (Amnis)
After abandoning the armed struggle at the end of the 1940’s, to protect the survival of the Spanish Libertarian Movement in exile (MLE), the FIJL was at the origin of the resumption of the anti-Franco fight. She emancipates herself from the libertarian organization and draws support from new generations of activists in favor of direct action in Spain. From 1961, Octavio Alberola joined Defensa Interior and certain members of the FIJL participated in the Iberian Liberation Committee (CIL), an organization considered terrorist by the French police services. Between 1962 and 1963, young libertarians participated in attacks affecting Spain and Europe, which mainly targeted international tourism and the Franco regime. The FIJL leads social protest and opposes the strengthening of international relations with the Spanish dictatorship. She denounces the “crimes” committed by Spain, such as the execution of Delgado and Granados in 1963 or that of Salvador Puig Antich in 1974, and maintains hope in the anti-Franco ranks.